2021
DOI: 10.1155/2021/9998480
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Care in Advanced Dementia from the Perspective of Health Providers: A Qualitative Systematic Review

Abstract: Background. Worldwide, 47 million people suffer from dementia. Despite recognizing the importance of spirituality within dementia care, it is still unclear how this should be integrated into dementia services. Aim. To explore the perspective of health professionals regarding the spiritual care of people with advanced dementia. Methods. A qualitative systematic review was performed following the Enhancing Transparency in Reporting the Synthesis of Qualitative Research guidelines for the study design. The inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Health-related barriers included behavioral expressions and incontinence of PLwDs, which inhibited staff from taking them to religious and spiritual activities. These barriers are not new but are also reported in other spiritual care provision articles [4,21,68,69].…”
Section: Spiritual Care Barriers To Addressing Spiritual Needsmentioning
confidence: 76%
See 2 more Smart Citations
“…Health-related barriers included behavioral expressions and incontinence of PLwDs, which inhibited staff from taking them to religious and spiritual activities. These barriers are not new but are also reported in other spiritual care provision articles [4,21,68,69].…”
Section: Spiritual Care Barriers To Addressing Spiritual Needsmentioning
confidence: 76%
“…In addition, caregivers of PLwDs often carry out multiple tasks while caring for their care recipients. Therefore, some essential aspects of care, such as spiritual needs, can be easily overlooked [3] or difficult to identify [4,5], especially in the later stage of dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All dimensions of a person must be taken into account in patient care; however, in palliative care patients, spiritual needs often take centre stage [26,27]. Spirituality is expressed in values, beliefs, and traditions and involves the pursuit and expression of meaning and purpose as well as a sense of connectedness to oneself, others, nature, or something that is meaningful or sacred to the individual [28].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, I would like to reaffirm that caring for human being’s spiritual lives is important if they are to flourish; this applies to all human beings, whatever their cognitive abilities. A qualitative systematic review conducted in 2021 [ 19 ] concluded that spirituality is still not formally addressed in elderly populations affected by dementia. Professionals still do not feel confident to integrate spirituality into their care.…”
Section: Discussionmentioning
confidence: 99%